(untitled) (Research, Society and Development, 2017)
The present study emphasized the importance of ludic playful for the development of the student with Down Syndrome. The main justification for this study was to seek and expand an important knowledge to educators, especially in the present times, in which the process of school inclusion is found. The objective of this study was to understand the importance of play for the integral development of children with Down Syndrome. The methodology used was the bibliographic review. We discussed, in this study, about Down Syndrome and its characteristics, as it was approached the relevance of playing for all children and we closed our discussion highlighting how important it is to play for the development of children, especially for the child with Down Syndrome. It was clear that playing brings important contributions to the stimulation of children with Down’s Syndrome. We consider relevant to emphasize that the ludic needs to be one of the instruments present within the classroom, in the teaching practice, contributing to the development of all children, including children with Down Syndrome. At the end of this study, we conclude that just as playing is essential for the development of all children without disabilities, it also becomes essential, especially for those with Down Syndrome, who need early stimulation in a playful and pleasurable way and contributing to their integral development and inclusion.